POSSIBILITIES FOR IMPROVING THE AGRICULTURAL EXTENSION SERVICE OF REPUBLIC OF SERBIA - Kostić, Stojan (Economics of Agriculture, 2010)
Agricultural extension service is one of the key factors of the agricultural and rural development. In this paper the author presents the main problems facing rural areas and agriculture of Serbia, as well as possibilities to improve AES, which would result in the reduction and resolution of these problems. Emphasis is placed on the extent of decentralization and implementation of "bottom-up" approach, funding, the creation of a pluralistic extension system, the need of additional education of staff, legislative and legal framework, as well as creation of a functional AKIS. Successful implementation of these measures and activities requires a great effort of agricultural experts, as well as the political will of the government.